2017
DOI: 10.1016/j.watres.2017.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of humic acid on the degradation of levofloxacin by aqueous permanganate: Kinetics and mechanism

Abstract: Levofloxacin (LF) is a frequently detected fluoroquinolone in surface water, and permanganate (MnO) is a commonly used oxidant in drinking water treatment. This study investigated the impact of humic acid (HA) on LF degradation by aqueous MnO from both kinetic and mechanistic aspects. In the absence of HA, the second-order rate constant (k) of LF degradation by MnO was determined to be 3.9 M s at pH 7.5, which increased with decreasing pH. In the presence of HA, the pseudo-first-order rate constant (k) of LF d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 31 publications
3
49
0
Order By: Relevance
“…Humic acid (HA) is a typical natural organic matter in real waters. In a previous study, HA was generally considered to have a positive role in the oxidation of organic contaminants in the KMnO 4 system. , In this study, HA can slightly accelerate the oxidation of SMX by KMnO 4 , and effects become more obvious with the increase of HA concentration (Figure a). Jiang et al revealed that HA, as a ligand, can stabilize intermediate Mn species formed by the reaction to enhance oxidation of triclosan by KMnO 4 …”
Section: Results and Discussionsupporting
confidence: 50%
“…Humic acid (HA) is a typical natural organic matter in real waters. In a previous study, HA was generally considered to have a positive role in the oxidation of organic contaminants in the KMnO 4 system. , In this study, HA can slightly accelerate the oxidation of SMX by KMnO 4 , and effects become more obvious with the increase of HA concentration (Figure a). Jiang et al revealed that HA, as a ligand, can stabilize intermediate Mn species formed by the reaction to enhance oxidation of triclosan by KMnO 4 …”
Section: Results and Discussionsupporting
confidence: 50%
“…Taking KMnO 4 /Na 2 S 2 O 3 system as an example, in order to explore the role of reactive radical species (e.g., HO·, SO3·-, SO4·-), DMPO was used to trap these plausible radicals. As shown in Figure , in the absence of Na 2 S 2 O 3 , DMPO was directly oxidized to DMPO‐OH by permanganate though there is no HO· generated, which is consistent with the literature (Xu et al, ; Xu, Dong, Li, & Qiang, ). The signal of DMPO‐OH was largely stifled when Na 2 S 2 O 3 was added since Na 2 S 2 O 3 could consume KMnO 4 , but there was no sign of sulfur‐containing radicals or hydroxyl radical.…”
Section: Resultssupporting
confidence: 90%
“…As for HA and Cl − , at low concentrations, they might compete with electrons in cathodes, resulting in the reduced generation of RMnS, whereas at higher concentrations they might react with RMnS to generate other reactive species (e.g., • OH, Cl • , etc.) to accelerate the MFC-PM process [24,48]. Additionally, the removal rate of DCF in urea solution was also evaluated to further assess the applicability of the MFC-PM process.…”
Section: Discussionmentioning
confidence: 99%